2007
DOI: 10.3121/cmr.2007.716
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin in Poststroke Spasticity

Abstract: Poststroke hemiparesis, together with abnormal muscle tone, is a major cause of morbidity and disability. Although most hemiparetic patients are able to reach different ambulatory levels with rehabilitation efforts, upper and lower limb spasticity can impede activities of daily living, personal hygiene, ambulation and, in some cases, functional improvement.The goals of spasticity management include increasing mobility and range of motion, attaining better hygiene, improving splint wear and other functional act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 62 publications
(47 reference statements)
0
49
0
5
Order By: Relevance
“…Bhakta et al (32) showed that the effects of BTX-A were sustained 11 months later in patients who were also involved in a regular rehabilitation program. Findings reported in some studies including a decrease in effectiveness at 12 months and differences in functional status may be caused by insufficient dose, patient selection, existence of contractures, and lack of effective and sufficient rehabilitation program (3,7,10). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhakta et al (32) showed that the effects of BTX-A were sustained 11 months later in patients who were also involved in a regular rehabilitation program. Findings reported in some studies including a decrease in effectiveness at 12 months and differences in functional status may be caused by insufficient dose, patient selection, existence of contractures, and lack of effective and sufficient rehabilitation program (3,7,10). …”
Section: Discussionmentioning
confidence: 99%
“…A maximum 100 points can be achieved. Patients with 0-20 points are considered as fully dependent, 21-61 points as highly dependent, 62-90 points moderately dependent, 91-99 points as mildly dependent, and 100 points as fully independent (10).…”
Section: Patient Populationmentioning
confidence: 99%
“…14 The introduction of BoNT-A has had a significant impact on the treatment of focal spasticity in the upper limbs, and it is widely viewed as a welltolerated and efficacious treatment option (when used appropriately, based on the relevant country-specific guidance and applicable summary of product characteristics) in conjunction with physical therapy programmes. 25,[34][35][36][37][38] Preliminary studies suggest that it is best delivered early, when spastic paresis first sets in, in order to minimise the development of secondary complications, such as contractures. 39 It is important to note that patients must also exercise and receive physical and occupational therapy, as long-term disuse can induce muscle atrophy.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Spasticity can negatively affect daily activities and a patient's physical appearance, balance, and gait pattern (2). Botulinum toxin (BTX) injection is a safe, effective, and commonly used method for the treatment of focal and multifocal spasticity.…”
Section: Introductionmentioning
confidence: 99%